Correlation and clinical significance of placental tissue selectin (E), angiotensin II and its receptors, and oxidized lipid levels in patients with preeclampsia: Preeclampsia: Placental Selectin, Angiotensin II, and Oxidized Lipids - Gao, Yan; Wu, Guohong; Huang, Haiting; Lu, Xiaoyan; Wu, Peifen; Zou, Suiyi; Liu, Zhenyan (Journal of Medical Biochemistry, 2024)
Background: The purpose was to analyze the levels of placental tissue selectins (E), angiotensin II (AngII) and its receptors (ATRs), and oxidized lipids (malondialdehyde (MDA), 8-isoprostane 2a) in patients with preeclampsia (PE). (8-iso-PGF2a)) correlation and clinical significance. Methods: Select 30 PE pregnant women who were admitted to our hospital from March 2023 to January 2024 as the case group, and select another 30 normal pregnant women who were registered in our hospital during the same period as the health group .The general information of the two groups and placental tissue selectin (E), plasma AngII, ATRs, placental tissue MDA, 8-iso-PGF2a and blood pressure levels (systolic blood pressure (SBP), diastolic blood pressure (DBP)) were compared. Pearson correlation was used to analyze the correlation between the expression of selectin (E), AngII, ATRs, MDA, 8-iso-PGF2a and the levels of SBP and DBP. Linear regression analysis was used to analyze the correlation between the expression of selectin (E), AngII, ATRs, MDA, 8-iso-PGF2a, SBP, DBP and other indicators and the occurrence of PE. ROC curves were drawn to analyze the value of placental tissue selectin (E), AngII, ATRs, MDA, and 8-iso-PGF2a individually and jointly in predicting the risk of PE. Results The expression of placental tissue selectin (E), AngII, ATRs, MDA, 8-iso-PGF2a and the levels of SBP and DBP in the case group were higher than those in the healthy group (P<0.05). Pearson correlation showed that the expression levels of placental tissue selectin (E), AngII, ATRs, MDA, and 8-iso-PGF2a were positively correlated with SBP and DBP (r>0, P<0.05). Linear regression analysis showed that placental tissue selectin (E), AngII, ATRs, MDA, 8-iso-PGF2a expression and SBP, DBP levels were closely related to the occurrence of PE (P<0.05). The results of drawing the ROC curve showed that the AUCs of placental tissue selectin (E), AngII, ATRs, MDA, and 8-iso-PGF2a expression in predicting the occurrence of PE were 0.854, 0.756, 0.745, 0.885, 0.900, and 0.905 respectively. Conclusion Placenta tissue selectin (E), AngII, ATRs, MDA, and 8-iso-PGF2a are highly expressed in pregnant women with PE. The expression of the above indicators is related to maternal blood pressure levels and the occurrence of PE, and their combination can effectively increase predictive value of the risk of PE.